Comparison of short-term and long-term renal function effects of vasopressin and norepinephrine in patients with septic shock: a systematic review and meta-analysis - Wang, Hongyu; Liu, Xilin; Zhang, Hong (Frontiers in Pharmacology, 2025)
BackgroundVasopressin and its derivatives, as second-line vasoactive agents, are increasingly being applied in the treatment of septic shock, but their effects on major organs, particularly the renal system, remain inadequately evaluated.MethodsA systematic search was conducted based on 4 online databases Embase, PubMed, ScienceDirect, and Scopus, for studies published up to April 2025 that compared the renal function outcomes between vasopressin versus norepinephrine. All the studies enrolled adult patients with septic shock. Both short-term outcomes (urine output, serum creatinine levels) and long-term outcomes (acute kidney injury (AKI) rate, renal failure (RF), days free of RF, and renal replacement therapy (RRT)-use rate) were assessed.ResultsA total of 13 studies met the inclusion criteria, comprising 10 RCTs and 3 retrospective cohort studies, with a total of 2,024 septic shock patients (aged 46.76–68 years) engaged. Meta-analysis showed no significant differences between the vasopressin and norepinephrine groups in the incidence of AKI (Risk Ratio (RR) = 1.07, 95% CI [0.86, 1.33], P = 0.53), days free of RF (MD = 1.52, 95% CI [−2.21, 5.25], P = 0.43), incidence of RF (RR = 1.01, 95% CI [0.85, 1.19], P = 0.94), or urine output (MD = −161.93 mL, 95% CI [−690.31, 366.45], P = 0.55). However, vasopressin was associated with a significantly lower serum creatinine level (MD = −0.15 mg/dL, 95% CI [−0.29, −0.02], P = 0.028) and a reduced RRT utilization rate (RR = 0.76, 95% CI [0.62, 0.93], P < 0.01) compared to norepinephrine.ConclusionVasopressin demonstrates potential renal protective effects in the management of septic shock, as evidenced by a significant reduction in serum creatinine levels and a decreased need for renal replacement therapy compared with norepinephrine. However, the evidence supporting its benefit in reducing the incidence of AKI and RF, or prolonging the days free of RF remains of low quality.